STUDI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA TERKAIT MATERI FAKTOR PERSEKUTUAN TERBESAR DAN KELIPATAN PERSEKUTUAN TERKECIL - Titik Pitriani; Abdul Rahim (Sigma: Jurnal Pembelajaran dan Pendidikan Matematika Sawerigading, 2023)
This research is a qualitative research by taking the subject of 4 students of class V SDN Sangir. This research focuse on the errors of students in solving story problems related to FPB and KPK. This study was conducted by collecting data from the results of written test and interviews with research subjects.The result of this research showed that there are several students' erorrs in solving story problems, including 1) The error of making mathematical models of story problems such as determining what is known or asked, 2) The error in troubleshooting, 3) The errors in the selection of operations in solving story problems, 4) The error in drawing conclusions. Based on the interview found several factors which has an effect on student errors are internal factors in the form of students’ knowledge, students’ interests, and motivation while the external factors while external factors are gender differences and environmental influences in schools.